A Systematic Review on Association of Oxidative Stress in Rheumatoid Arthritis Based on Cross-Sectional Case-Control Studies - Ahmed, Abdul Baquee; Chetia, Purbajit; Kalita, Hemen (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Rheumatoid Arthritis (RA) is a chronic form of inflammatory disorder where the immune system causes the destruction of bones and cartilage in joints and impacts the quality of life. Few studies have explored the possibility of the involvement of oxidative stress markers in the pathophysiological process of disease progression in RA as well as the beneficial effect of antioxidants. It was discovered that no systematic review had been carried out to support this idea over the previous five years. Aim This review is intended to analyse the participation of oxidative stress markers in the origination and development of RA so that they can be a potential biomarker for supportive therapy. Materials and Methods This systematic review was carried out as per the PRISMA guidelines. The authors executed a systematic literature search in different search engines for cross-sectional case-control research studies during the period from January 1, 2018 to November 30, 2022. Following inclusion and exclusion criteria, 16 articles have been selected for final analysis. Results The evaluated biomarkers in the aforementioned studies countenance the participation of oxidative stress in RA with disease progression. However, additional research will be needed in the future to determine how oxidative stress contributes to the progression of RA and the potential role of antioxidants. Conclusion Oxidation biomarkers may be an important tool in the early diagnosis of RA starting at the preclinical stage as well as in determining how the disease is evolving, offering new promise for employing these biomarkers as a focal point for supportive therapy.
Keywords: Rheumatoid Arthritis; Biomarkers; Malonandehyde; ROS; Oxidative Stress; SOD